Offshore moorings proceedings of a conference organised by the Institution of Civil Engineers and held in East Kilbride on 10 March 1982. (Thomas Telford, 1982)
Environmental loading and response is discussed within these papers, as well as moored production and loading facilities as experienced at the Argyll Field. A state-of-the-art assessment of high capacity sea floor anchors is considered.